Pemodelan Implementasi Business Intelligence pada Proses Evaluasi Kurikulum di Fakultas Teknologi Informasi Universitas Atma Jaya Makassar - Stacey Marchlyana Tayu; Elisabeth (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2022)
One measure of the success of education in higher education so that it can compete with other universities and answer industry needs from time to time can be seen from the number and quality of alumni produced. Alumni play an important role not only as a tool to measure the ability to implement and the quality of their education programs, but alumni are also important as a source of input or feedback for improving the education system in the preparation of curriculum in universities. In curriculum development, evaluation is one of the important components and stages that must be taken by the teacher to determine the effectiveness of the curriculum. Evaluation is an integral part of the curriculum. Evaluation is part of the management system, namely planning, organization, implementation, monitoring and evaluation. This study aims to model an implementation of Business Intelligence at the Atma Jaya Makassar University Faculty of Information Technology (FTI UAJM). This is intended to help the FTI UAJM in the curriculum evaluation process to obtain learning objectives that can be used to improve the skills of students by processing existing data into valuable information. The results of this study are a modeling of the implementation of Business Intelligence to support the curriculum evaluation process Intelligence at the Atma Jaya Makassar University Faculty Of Information Technology (FTI UAJM).